Exercise has persistent effects on learning and memory throught the lifespan: Analysis of the underlying mechanisms - MOTA, BIBIANA CASTAGNA (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2018)
Ageing is a complex process associated with a decline in organism functions. Ageing affects several cellular and molecular brain mechanisms and is commonly associated with decline in brain function, such as cognition and emotion Moreover, age is characterised by the presence of chronic and low-grade inflammation, which is associated with decreased responsiveness of immune cells to stress and exacerbated inflammatory response. However, sometimes, even though morphological and physiological changes are observed in the brain of aged individuals, they may not experience the cognitive decline usually associated with ageing. In an attempt to explain this discrepancy between an individual's measured level of brain pathology/or age-related changes and the functional and/or cognitive deficits that are expected to result from that pathology or from normal ageing, the cognitive reserve hypothesis was proposed. Evidence suggest that life exposure and experiences can build brain reserve, by increasing brain resources and making the brain more flexible and capable of recruiting theses resources. In this context, exposure to physical exercise is associated with positive inflammatory modulation and increased brain plasticity, thereby contributing to reduce the unfavourable effects of ageing. Therefore, the overall aim of this study is to investigate the effects of forced exercise on memory and learning throughout the mouse lifespan, investigating the cellular mechanisms involved and the reserve hypothesis. Firstly, we investigated the effects of long-term forced exercise, during youth and middle-age, on learning and memory throughout the lifespan of the mouse, and its effects on age-related anxiety and depression like behaviour, investigating the mechanisms involved in these effects. Secondly, as inflammation was demonstrated to be participating in the pro-cognitive effects of exercise, we decided to address the effects of short-term forced exercise on memory, inflammatory responses and activation of isolated populations of microglia and astrocytes, in a mouse model of neuroinflammation. To respond our first question, young male mice underwent treadmill running for a period of 8 months until middle-age, when they stopped exercising. After that, mice were housed in the absence of exercise for 10 more months until old age. All mice were tested every 2 months for non-spatial (NOR) and spatial memory (OD) and at old age they were tested in the MWM and underwent analysis of anxiety and depression-like behaviour. Subsequently, structural MRI was performed, tissue was collected, and glial cells were isolated from the brain tissue. Assessment of BrdU labelling and cell phenotype by immunohistochemistry were used to investigate neurogenesis and assay of mRNA and protein expression of different targets of interest, focusing mainly in inflammatory markers, were carried out. To answer our second question, mice underwent 9 consecutive days of treadmill running prior to a single intraperitoneal injection of a sub-septic dose of lipopolysaccharide. Four hours later, mice were tested for spatial learning and memory and brain tissue was removed for analysis of inflammatory response and glia cells activation. Our results demonstrated that exercise has an important effect in enhancing cognition and emotional behaviour as well as protecting against cognitive impairments in non-spatial and spatial memory, even months after exercise cessation. Moreover, exercise protected against LPS-induced impairment in spatial memory. We demonstrated that these cognitive improvements were mediated in large part by the anti-inflammatory effects of exercise, which positively modulated the brain environment protecting against the disruption of brain mechanism structure and function induced by neuroinflammation and age. The anti-inflammatory effect of exercise was shown to be directly involved in the preservation and enhancement of the mechanisms of hippocampal neurogenesis and synaptogenesis induced by exercise in our study and consequently the protection of the integrity of important brain regions. We propose that collectively these changes contribute to building a cognitive reserve and rendering the brain more resilient, thereby mediating protection against cognitive decline during the ageing process.
APPROVED
Keywords: inflammation; exercise; neurogenesis; mouse; microglia; astrocytes; ageing